2007
DOI: 10.1021/ja070243s
|View full text |Cite
|
Sign up to set email alerts
|

An Extremely Effective DNA Photocleavage Utilizing Functionalized Liposomes with a Fullerene-Enriched Lipid Bilayer

Abstract: A surface-functionalized liposome with a high C70 concentration (LMIC70) was synthesized by exchange reaction from an unstable fullerene complex, C70·γ-CDx. The DNA photocleavage ability of LMIC70 is extremely higher than that of LMIC60 or C60·γ-CDx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
94
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 25 publications
0
94
0
3
Order By: Relevance
“…51 Liu and coworkers 52 used a water soluble conjugate between anthrylcyclodextrin and C 60 to carry out photocleavage of pGEX5x2 DNA. Ikeda et al 53 used functionalized liposomes encorporating both C 60 and C 70 fullerenes into the lipid bilayer to carry out photocleavage of ColE1 supercoiled plasmid DNA using λ > 350 nm light. Interestingly C 70 was significantly better (3.5 times) than C 60 in photocleaving DNA.…”
Section: Dna Cleavage and Mutagenicitymentioning
confidence: 99%
“…51 Liu and coworkers 52 used a water soluble conjugate between anthrylcyclodextrin and C 60 to carry out photocleavage of pGEX5x2 DNA. Ikeda et al 53 used functionalized liposomes encorporating both C 60 and C 70 fullerenes into the lipid bilayer to carry out photocleavage of ColE1 supercoiled plasmid DNA using λ > 350 nm light. Interestingly C 70 was significantly better (3.5 times) than C 60 in photocleaving DNA.…”
Section: Dna Cleavage and Mutagenicitymentioning
confidence: 99%
“…Light-harvesting liposomes of LMIC 60 -DiD were prepared via fullerene exchange from the γ-cyclodextrin (γ-CDx) cavity to DiD contained liposomes (liposome-DiD) following a previously reported method. [10][11][12][13] Due to the efficient intracellular uptake of liposomes by tumor cells in our previously reports, liposomes with cationic surfaces were used for the preparation of LMIC 60 -DiD. 10,11 The structures of DiD and lipids are shown in Figure S1 in the Supporting Information.…”
mentioning
confidence: 99%
“…1,2 Due to the formation of a long-lived triplet state and the high photoproduction ability of ROS, fullerenes have attracted significant attention as PS of PDT. [3][4][5][6][7][8][9][10][11][12][13] We have previously reported that liposomal lipid membrane can be used for solubilization of unmodified [60]fullerenes (C 60 ) to overcome their poor water solubility. The produced cationic lipid membrane incorporating C 60 (LMIC 60 ) showed high cytotoxicity under light irradiation between 350-500 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…121 Outros estudos com derivados fulerênicos, visando a aplicação na TFD, foram realizados. 119,[124][125][126][127][128][129][130] Observa-se claramente que o ponto central destes trabalhos é a busca por compostos mais hidrossolúveis. Neste contexto, podemos destacar os derivados fulerênicos contendo sacarídeos sintetizados por Mikata et al 130 (Figura 15).…”
Section: Uso Em Terapia Fotodinâmicaunclassified